Pharmacological Inhibition of IRE-1 Alpha Activity in Herpes Simplex Virus Type 1 and Type 2-Infected Dendritic Cells Enhances T Cell Activation - Tognarelli, Eduardo I.; Retamal-Díaz, Angello; Farías, Mónica A.; Duarte, Luisa F.; Palomino, Tomás F.; Ibañez, Francisco J.; Riedel, Claudia A.; Kalergis, Alexis M.; Bueno, Susan M.; González, Pablo A. (Frontiers in Immunology, 2022)
Herpes simplex virus type 1 (HSV-1) and type 2 (HSV-2) infections are life-long and highly prevalent in the human population. These viruses persist in the host, eliciting either symptomatic or asymptomatic infections that may occur sporadically or in a recurrent manner through viral reactivations. Clinical manifestations due to symptomatic infection may be mild such as orofacial lesions, but may also translate into more severe diseases, such as ocular infections that may lead to blindness and life-threatening encephalitis. A key feature of HSVs is that they have evolved molecular determinants that hamper numerous components of the host’s antiviral innate and adaptive immune system. Importantly, HSVs infect and negatively modulate the function of dendritic cells (DCs), by inhibiting their T cell-activating capacity and eliciting their apoptosis after infection. Previously, we reported that HSV-2 activates the splicing of the mRNA of XBP1, which is related to the activity of the unfolded protein response (UPR) factor Inositol-Requiring Enzyme 1 alpha (IRE-1α). Here, we sought to evaluate if the activation of the IRE-1α pathway in DCs upon HSV infection may be related to impaired DC function after infection with HSV-1 or HSV-2. Interestingly, the pharmacological inhibition of the endonuclease activity of IRE-1α in HSV-1- and HSV-2-infected DCs significantly reduced apoptosis in these cells and enhanced their capacity to migrate to lymph nodes and activate virus-specific CD4+ and CD8+ T cells. These findings suggest that the activation of the IRE-1α-dependent UPR pathway in HSV-infected DCs may play a significant role in the negative effects that these viruses exert over these cells and that the modulation of this signalling pathway may be relevant for enhancing the function of DCs upon infection with HSVs.